Analisis Penerapan Aplikasi SIMDA BMD Dalam Meningkatkan Akuntabilitas Kinerja Pegawai Guna Memaksimalkan Pemanfaatan Aset Daerah : Studi Kasus BKAD Kabupaten Bintan - Fauzan Fadillah Di Harjo; Desfina Desfina (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Planning and reporting performance results in local government using information systems. The purpose of conducting research is to obtain an overview of the results of accountability for employee performance with the help of implementing SIMDA BMD at the Regional Financial and Asset Agency of the Bintan Regency Government. It is hoped that the presence of the SIMDA application can help the government in managing finances, especially in employee performance accountability and providing ideal management information. Data collection was collected using literature studies, interviews, observation and documentation. The results of this research show that SIMDA BMD (Regional Property Management Information System) in the financial management process, especially financial reporting, continues to run well and cannot yet be said to be fully effective, this is due to various obstacles that occur.